Maternal depression and suicide at immediate prenatal and early postpartum periods and psychosocial risk factors. (March 2018) - Shi, Peixia; Ren, Hui; Li, Hong; Dai, Qin
Abstract: Maternal depression has been intensively explored; however, less attention has been paid to maternal suicide. No studies to date have observed maternal depression and suicide at immediate prenatal and early postpartum stages. In total, 213 Chinese women were recruited in hospitals after they were admitted for childbirth. All completed a short-term longitudinal survey at perinatal stages. Women reported lower depression scores (6.65) and higher suicidal ideation incidence (11.74%) after childbirth. Prenatal depression raised the possibility of prenatal suicidal ideation, while prenatal depression and suicidal ideation increased postpartum depression and suicidal ideation. At immediate prenatal stage, marital satisfaction protected women from depression, while miscarriage experiences and self-esteem increased the risk. At early postpartum stage, in contrast, being first-time mother, marital satisfaction, and harmony with mother-in-law prevented them from depression. Our study is among the first to confirm that women have decreased depression but increased suicidal ideation at early postpartum, and a causal relationship between them, which are worthy of public attention. Potential protective (marital satisfaction, being first-time mother, and harmony with mother-in-law) or risk factors (miscarriage experiences and self-esteem) of maternal depression and suicidal ideation are identified at perinatal stages. This offers reliable guidance for clinical practice of health care. Highlights: Women had lower depression and higher suicidal ideation after childbirth. Depression and suicidal ideation interrelated at prenatal and postpartum stages. Marital dissatisfaction and miscarriage experiences increased the risk of depression. Being first-time mother, harmony with husband and mother-in-law, protected women.